2017
DOI: 10.1038/s41598-017-02929-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity of epoxy composites filled with silicon carbide nanowires

Abstract: In this study, we report a facile approach to fabricate epoxy composite incorporated with silicon carbide nanowires (SiC NWs). The thermal conductivity of epoxy/SiC NWs composites was thoroughly investigated. The thermal conductivity of epoxy/SiC NWs composites with 3.0 wt% filler reached 0.449 Wm−1 K−1, approximately a 106% enhancement as compared to neat epoxy. In contrast, the same mass fraction of silicon carbide micron particles (SiC MPs) incorporated into epoxy matrix showed less improvement on thermal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 75 publications
2
58
0
1
Order By: Relevance
“…The filler content is the most frequently discussed influential factor, and only a very few studies have explored the temperature influence. A recent work shows that the κ of epoxy composites containing 3 wt% of SiC NWs increases with temperature . Figure b summarizes the thermal conductivity of polymer composites reinforced by different ceramic nanofillers.…”
Section: Polymer Composites With Nanostructured Fillers For High Thermentioning
confidence: 99%
“…The filler content is the most frequently discussed influential factor, and only a very few studies have explored the temperature influence. A recent work shows that the κ of epoxy composites containing 3 wt% of SiC NWs increases with temperature . Figure b summarizes the thermal conductivity of polymer composites reinforced by different ceramic nanofillers.…”
Section: Polymer Composites With Nanostructured Fillers For High Thermentioning
confidence: 99%
“…Gu et al [26,27] fabricated the corresponding thermally conductive SiC/PS composites by the method of Belectrospinning-laminating-hot press.T he addition of 32.8 vol% SiCp could improve the λ value of pure PS from 0.182 to 0.566 W/mK. Shen et al [173] reported a facile approach to fabricate epoxy composites incorporated with silicon carbide nanowires (SiC NWs) and silicon carbide micron particles (SiC MPs), respectively. The λ value of the SiC NWs/epoxy composite was increased to 0.449 W/mK with 3.0 wt% SiC NWs, higher than that of the SiC MPs/epoxy composite filled with the same addition of SiC MPs.…”
Section: Sicmentioning
confidence: 99%
“…The thermal conductivity obtained for the thermal interface materials also agrees with that measured using the in-house steady-state divided bar method (Nanotest TIMA). The relative [26] 0.04 ± 0.03 0.068 [26], [27], [28] PDMS 0.15 ± 0.01 0.16 [41], 0.26 [42], 0.21 [43] 0.06 ± 0.01 -Epoxy (cured) 0.22 ± 0.02 0.23 ± 0.02 [*], 0.2 [44], [45] 0.11 ± 0.03 0.06-0.24 [45], [46] Glycerol 0.27 ± 0.01 0.285 [47] 0.06 ± 0.03 0.099 [29]…”
Section: -Omega Measurement Results For Reference Materialsmentioning
confidence: 99%